1991
DOI: 10.1111/j.1744-7976.1991.tb03560.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Wheat a Homogeneous Product?

Abstract: A hedonic approach is used to test for two kinds of product differentiation for wheat. It is shown that wheat is differentiated by end use and by country of origin. This simply recognizes the fact that buyers purchasing wheat for different purposes put different weights on quality criteria and that country‐specific factors such as weather as well as grading and inspection systems matter. The results suggest that between 1980 and 1988, wheat protein content had a significant influence on price. This influence v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 9 publications
(15 reference statements)
3
43
0
Order By: Relevance
“…Finally, the finding of no cointegration between the three representative wheats belonging to each sub-market indicates that the wheats from each sub-market form no long-run relationship given their distinct end uses. This finding supports the contention that wheat should be differentiated according to end use in econometric modeling (Veeman 1987, Wilson 1989, Larue 1991.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Finally, the finding of no cointegration between the three representative wheats belonging to each sub-market indicates that the wheats from each sub-market form no long-run relationship given their distinct end uses. This finding supports the contention that wheat should be differentiated according to end use in econometric modeling (Veeman 1987, Wilson 1989, Larue 1991.…”
Section: Resultssupporting
confidence: 79%
“…Different classes of wheat have different end uses and are not always considered as close substitutes (Antle and Smith 1999). For instance, the Canadian Western Red Spring wheat is considered to be a high quality wheat and generally commands a premium on the world market (Larue 1991). For any other class of wheat to be substitutable, the two classes of wheat would need to be perceived by the consumer as being of similar end use and closely priced.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They found both quality differentials and prices were competitive factors in international markets. Larue (1991) investigated several issues related to wheat quality for Australia, Canada and the USA. Estimating a hedonic price model, he suggested that product differentiation by country of origin and end use was important and that average annual wheat prices were influenced by protein content.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of studies on this subject in the international literature differ, the protein content seems to be the common and most important characteristic quality in the determination of wheat prices (Veeman 1987;Mercier 1993;Uri and Hyberg 1996). Larue (1991) showed that the marginal implicit value of protein varied depending on the wheat classification and in time. Wilson (1989) demonstrated that it could change depending on the destination market (Stingert and Blane 1997) analysed the demand for the wheat protein in relation to five classes of wheat Hedonic price analysis of the quality characteristics of the Anatolian Hard Red Wheat in the Japanese import market.…”
mentioning
confidence: 99%